2020
DOI: 10.1515/ip-2020-4004
|View full text |Cite
|
Sign up to set email alerts
|

Tact or frankness in English and Russian blind peer reviews

Abstract: In a context of increasing globalization of academic discourse, considerations of the impact of culture on different communicative genres and discursive practices become more relevant than ever, as the construction of pragmatic meaning and its appropriate interpretation by the recipient is seen to depend on lexico-grammatical features whose use is greatly affected by cultural factors. This paper concerns the genre of blind peer review, and examines how disagreement and negative evaluation are expressed in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 76 publications
0
3
0
2
Order By: Relevance
“…However, studies have suggested that politeness relies on various communicative styles and expressive traditions, which manifest variations across cultures (Larina and Ponton, 2020). In response to the reviewed literature, there is a need to investigate the 'elusive' nature of politeness (Culpeper, 2013).…”
Section: Politeness Values and Cultural Dynamicsmentioning
confidence: 99%
“…However, studies have suggested that politeness relies on various communicative styles and expressive traditions, which manifest variations across cultures (Larina and Ponton, 2020). In response to the reviewed literature, there is a need to investigate the 'elusive' nature of politeness (Culpeper, 2013).…”
Section: Politeness Values and Cultural Dynamicsmentioning
confidence: 99%
“…Both politeness and impoliteness involve the study of communicative behavior in social interaction with a focus on situational and cultural contexts (e.g. Alemi & Latifi 2019, Bousfield 2008, Eslami 2005, Fernández-Amaya 2019, Kaul de Marlangeon 2018, Larina & Ponton 2020, Lewandowska-Tomaszczyk & Pęzik 2021, Locher 2013, Tzanne & Sifianou 2019. The discursive turn contributed to understanding the evaluative and situated nature of im/politeness, the importance of emotions in assessments and the link of identity construction with these discourse aspects (Locher & Larina 2019: 875).…”
Section: Im/politeness In Cross-cultural Perspectivementioning
confidence: 99%
“…И вежливость, и невежливость предполагают изучение коммуникативного поведения в социальном взаимодействии с учетом ситуативного и культурного контекста (e.g. Alemi & Latifi 2019, Bousfield 2008, Eslami 2005, Kaul de Marlangeon 2018, Fernández-Amaya 2019, Larina & Ponton 2020, Lewandowska-Tomaszczyk & Pęzik 2021, Locher 2013, Tzanne & Sifianou 2019. Дискурсивный поворот способствовал пониманию оценочно-ситуативной природы не/вежливости, важности эмоций в их оценке и связи этих процессов с конструированием идентичности (Locher & Larina 2019: 886).…”
Section: не/вежливость в кросс-культурном аспектеunclassified
“…A systematic study and a comprehensive analysis of the communicative behavior of people belonging to different cultures will help us explain the codes and the underlying reasons for various do's and don'ts of the cultures that are not our own. This requires development of new integrative methodologies and promises a variety of applications in different spheres of human activities (see Besemeres & Wierzbicka 2007, Bromhead & Ye 2020, Dewaele 2010, Kabakchi & Proshina 2021, Kecskes 2014, Klyukanov & Leontovich 2016, Larina 2015, Larina et al 2016, Larina & Ponton 2020, Malyuga & McCarthy 2018, 2020, Wierzbicka 2003/1991, 2012, 2020.…”
Section: редакционная статьяmentioning
confidence: 99%
“…Для их решения необходимо системное исследование взаимодействия языка, культуры, менталитета и коммуникации, всесторонний анализ особенностей коммуникативного поведения представителей различных культур и выявление их причин, а также разработка методологий подобных исследований (см. Besemeres & Wierzbicka 2007, Bromhead & Ye 2020, Dewaele 2010, Kecskes 2014, Klyukanov & Leontovich 2016, Larina 2015, Larina et al 2016, Larina & Ponton 2020, Malyuga & McCarthy 2018, 2020, Wierzbicka 2003/1991, 2012, 2020.…”
Section: Ruunclassified